Malignant melanoma and radiotherapy: past myths, excellent local control in 146 studied lesions at Georgetown University, and improving future management - Jahanshahi, Pooya; Nasr, Nadim; Unger, Keith; Batouli, Ali; Gagnon, Gregory J. (Frontiers in Oncology, 2012)
Introduction: Once thought to be radioresistant, emerging cellular and clinical evidence now suggests melanoma can respond to large radiation doses per fraction. Materials and Methods: We conducted a retrospective study of all patients treated with stereotactic radiosurgery and stereotactic body radiotherapy at Georgetown University Hospital from May 2002 through November 2008 and studied the classic Extrapolated Total Dose Corrected for Volume (ETDvol) model for predicting melanoma tumor response. Region-specific tumor outcomes were categorized by RECIST criteria and local control curves were estimated and analyzed when stratified by ETDvol thresholds by use of the Kaplan-Meier method. Results: Follow-up information was available for 78 lesions (49 intracranial, 8 spinal, and 21 body) with mean follow-up period of 9.2 (range, 2-36) months. 1-year local control rates for intracranial, spinal, and body tumors were 84%, 100%, and 72% respectively. Treatments in general were well-tolerated. Increased ETDvol (p<0.001) among intracranial sites resulted from larger (p<0.001) doses per fraction combined with smaller (p<0.001) tumor diameters. Intracranial 6-, 12-, and 24-month local control rates when treated above ETDvol threshold of 230 Gy were all 90% vs. 89%, 80%, and 53% below this threshold. Body 6- and 12-month local control rates when treated above ETDvol threshold of 100 Gy were 100% and 80% vs. 74% and 59% below this threshold. Discussion: By tailoring to melanoma’s unique radiobiology with large radiation doses per fraction, favorable local control was safely achieved. The ETDvol model combines the important factor of dose per fraction in melanoma treatment with a volume correction factor to predict tumor response. Although limited sample size may have prevented reaching statistical significance for local control improvements using ETDvol thresholds, optimal thresholds may exist to improve future tumor responses and further research is required.